2006
DOI: 10.1165/rcmb.2005-0314oc
|View full text |Cite
|
Sign up to set email alerts
|

Multistrain Genetic Comparisons Reveal CCR5 as a Receptor Involved in Airway Hyperresponsiveness

Abstract: Asthma is a ubiquitous disease with a broad range of clinical phenotypes. To better understand the complex genetic and environmental interactions underlying asthma, we compared the gene-gene interactions of four genetically distinct mouse strains that demonstrate biologically distinct responses to allergen. Using DNA microarrays and knock-out mouse studies, we showed that CCR5 plays a definitive role in the development of ovalbumin-induced allergic airway inflammatory disease. In addition, gene expression prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
10
1
Order By: Relevance
“…Hence 34% (54/161) of the genes were shared by both strains. The list of shared genes includes Arg1, Agr2, Clca3, Muc5ac, Ccl8, Ccl11, Chi3L3, Chi3L4, Chia, Scin, Retnla, Retnlb, Timp, Ear11, Mgl1, Saa3, Serpina3n, and Slc6a24, which were previously described in murine studies (15)(16)(17)(18)(19)(20)(21)(22), adding further support to a role for these genes in allergic airway disease. A subset of these genes was evaluated and confirmed by quantitative RT-PCR (Table E4).…”
Section: Gene Expression Analysis Reveals Shared and Distinct Patternmentioning
confidence: 64%
See 1 more Smart Citation
“…Hence 34% (54/161) of the genes were shared by both strains. The list of shared genes includes Arg1, Agr2, Clca3, Muc5ac, Ccl8, Ccl11, Chi3L3, Chi3L4, Chia, Scin, Retnla, Retnlb, Timp, Ear11, Mgl1, Saa3, Serpina3n, and Slc6a24, which were previously described in murine studies (15)(16)(17)(18)(19)(20)(21)(22), adding further support to a role for these genes in allergic airway disease. A subset of these genes was evaluated and confirmed by quantitative RT-PCR (Table E4).…”
Section: Gene Expression Analysis Reveals Shared and Distinct Patternmentioning
confidence: 64%
“…Shibamori and colleagues (37) used Der f extract in repeated intranasal sensitizations, and observed increased AHR after a single challenge with 100 mg of Der f. Tournoy and Schou (26) achieved increased AHR in this strain by sensitizing mice with Der p 1 plus alum with a chronic challenge protocol (Days [14][15][16][17][18][19][20]. Importantly, others showed that the addition of adjuvant, namely alum, initiates a distinct inflammatory response involving the inflammosome (38).…”
Section: Discussionmentioning
confidence: 99%
“…The gene for one of the antioxidant proteins, peroxiredoxin, was one of the most strongly up-regulated genes in Pneumocystis-infected BALB/c mice. Although this might act as a protective agent in the presence of oxidants, peroxiredoxins also are implicated in the modification of immune cells function (45) as well as the onset of AHR in mice (46). Another interesting gene on this list is CD38.…”
Section: Discussionmentioning
confidence: 99%
“…Walker and colleagues (14) reported that CCR5 2/2 mice showed lower AHR, but the numbers of eosinophils in CCR5 2/2 mice were similar to those in CCR5 1/1 mice. In contrast, in the current study, CCR5…”
Section: Sensitized T Cells Obtained From Ccr5mentioning
confidence: 96%
“…Downregulation of CCR5 by a compound and a chemokine ligand suppressed AHR and airway inflammation (12,13). However, it has also been shown that CCR5 regulates the development of AHR, but not eosinophilic inflammation in a mouse model of allergen-induced airway responses (14). Thus, CCR5 might control allergic airway responses, but its role in airway inflammation is controversial.…”
mentioning
confidence: 99%